PSMA PET in Imaging Prostate Cancer - Tsechelidis, Ioannis; Vrachimis, Alexis (Frontiers in Oncology, 2022)
After prostate malignancy diagnosis, precise determination of disease extent are fundamental steps for tailored made therapy. The earlier the diagnosis of the burden of the disease, the longer the survival in many cases. National and international guidelines are based on “classic” imaging technics combining radiological and nuclear medicine scans like CT, MRI and bone scintigraphy (BS). The most recent nuclear medicine development is the prostate specific membrane antigen (PSMA) PET and is emerging as the most promising tool of medical imaging, gaining ground every day. Nevertheless, the different onset among multiple studies fails to establish a worldwide admission and incorporation of this technique in guidelines and its position in workaday medical algorithms. It seems that the medical community agrees not to utilize PSMA PET for low-risk patients; intense debate and research is ongoing for its utility in intermediate risk patients. Contrariwise, in high-risk patients PSMA PET is confirmed outperforming CT and BS combined. Additionally, irrespectively to their castration status, patients with biochemical failure should be referred for PSMA PET. Even though PSMA PET reveals more extended disease than expected or exonerates equivalent lesions, thus impacting treatment optimization. Studies being in progress and future trials with clarify whether PSMA PET will be the new gold standard technic for specific groups of patients.